Electrophilic Fatty Acid Species Inhibit 5-Lipoxygenase and Attenuate Sepsis-Induced Pulmonary Inflammation - Awwad, Khader (Mary Ann Liebert, Inc., 2014)
Aims: The reaction of nitric oxide and nitrite-derived species with polyunsaturated fatty acids yields electrophilic fatty acid nitroalkene derivatives (NO(2)-FA), which display anti-inflammatory properties. Given that the 5-lipoxygenase (5-LO, ALOX5) possesses critical nucleophilic amino acids, which are potentially sensitive to electrophilic modifications, we determined the consequences of NO(2)-FA on 5-LO activity in vitro and on 5-LO-mediated inflammation in vivo. Results: Stimulation of human polymorphonuclear leukocytes (PMNL) with nitro-oleic (NO(2)-OA) or nitro-linoleic acid (NO(2)-LA) (but not the parent lipids) resulted in the concentration-dependent and irreversible inhibition of 5-LO activity. Similar effects were observed in cell lysates and using the recombinant human protein, indicating a direct reaction with 5-LO. NO(2)-FAs did not affect the activity of the platelet-type 12-LO (ALOX12) or 15-LO-1 (ALOX15) in intact cells or the recombinant protein. The NO(2)-FA-induced inhibition of 5-LO was attributed to the alkylation of Cys418, and the exchange of Cys418 to serine rendered 5-LO insensitive to NO(2)-FA. In vivo, the systemic administration of NO(2)-OA to mice decreased neutrophil and monocyte mobilization in response to lipopolysaccharide (LPS), attenuated the formation of the 5-LO product 5-hydroxyeicosatetraenoic acid (5-HETE), and inhibited lung injury. The administration of NO(2)-OA to 5-LO knockout mice had no effect on LPS-induced neutrophil or monocyte mobilization as well as on lung injury. Innovation: Prophylactic administration of NO(2)-OA to septic mice inhibits inflammation and promotes its resolution by interfering in 5-LO-mediated inflammatory processes. Conclusion: NO(2)-FAs directly and irreversibly inhibit 5-LO and attenuate downstream acute inflammatory responses. Antioxid. Redox Signal. 20, 2667–2680.